Clinical phase I/II trial to investigate neoadjuvant intensity-modulated short term radiation therapy (5 × 5 gy) and intraoperative radiation therapy (15 gy) in patients with primarily resectable pancreatic cancer - NEOPANC - Röder, Falk; Timke, Carmen; Saleh-Ebrahimi, Ladan; Schneider, Lutz; Hackert, Thilo; Hartwig, Werner; Kopp-Schneider, Annette; Hensley, Frank W.; Büchler, Markus W.; Debus, Jürgen; Huber, Peter E.; Werner, Jens (BMC cancer, 2012)
The current standard treatment, at least in Europe, for patients with primarily resectable tumors, consists of surgery followed by adjuvant chemotherapy. But even in this prognostic favourable group, long term survival is disappointing because of high local and distant failure rates. Postoperative chemoradiation has shown improved local control and overalls survival compared to surgery alone but the value of additional radiation has been questioned in case of adjuvant chemotherapy. However, there remains a strong rationale for the addition of radiation therapy considering the high rates of microscopically incomplete resections after surgery. As postoperative administration of radiation therapy has some general disadvantages, neoadjuvant and intraoperative approaches theoretically offer benefits in terms of dose escalation, reduction of toxicity and patients comfort especially if hypofractionated regimens with highly conformal techniques like intensity-modulated radiation therapy are considered.